2017
DOI: 10.1007/s00221-017-5149-3
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilesional functional recruitment within lower mu band in children with unilateral cerebral palsy, an event-related desynchronization study

Abstract: Cerebral palsy (CP) is a group of non-progressive developmental movement disorders inducing a strong brain reorganization in primary and secondary motor areas. Nevertheless, few studies have been dedicated to quantify brain pattern changes and correlate them with motor characteristics in CP children. In this context, it is very important to identify feasible and complementary tools able to enrich the description of motor impairments by considering their neural correlates. To this aim, we recorded the electroen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
2
7
0
1
Order By: Relevance
“…The highest percentages of individuals with CP were in the DM and PF clusters, both of which had appreciably lower percentages in TD. These results suggest an under-reliance on the NDM region and an over-reliance on the PF and DM regions in CP, which is not surprising based on upper limb studies that demonstrate a reorganization that favors use of the dominant hemisphere over the non-dominant one in both unilateral non-dominant side and bilateral tasks (Kukke et al, 2015;Inuggi et al, 2018;Weinstein et al, 2018). These results may also be attributed to the elevated functional role of the dominant limb during walking in our cohort, as evidenced by increased dominant limb stance time and cadence compared to the non-dominant side.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The highest percentages of individuals with CP were in the DM and PF clusters, both of which had appreciably lower percentages in TD. These results suggest an under-reliance on the NDM region and an over-reliance on the PF and DM regions in CP, which is not surprising based on upper limb studies that demonstrate a reorganization that favors use of the dominant hemisphere over the non-dominant one in both unilateral non-dominant side and bilateral tasks (Kukke et al, 2015;Inuggi et al, 2018;Weinstein et al, 2018). These results may also be attributed to the elevated functional role of the dominant limb during walking in our cohort, as evidenced by increased dominant limb stance time and cadence compared to the non-dominant side.…”
Section: Discussionmentioning
confidence: 64%
“…To our knowledge, this is the first EEG study of walking in CP as well as in a healthy pediatric cohort. In upper limb tasks, EEG-based studies have found that, compared to children with typical development, individuals with child-onset brain injury (before age 13) have reduced ERD in the affected hemisphere during wrist extension (Kukke et al, 2015), hand grasping (Weinstein et al, 2018), and reach to grasp (Inuggi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…If children with uCP with a larger variability in the degree of sensorimotor skills were to be included, one could expect a corresponding variability in the performance in the active position sense assessment within the uCP group. This is because mild-to-moderately severely affected children with uCP may benefit from ipsilesional neuroplastic reorganization enhancing residual motor abilities, which may result in a better performance in active position sense assessment when compared to a more severely affected uCP group (Inuggi et al, 2018 ). More research on the performance on this task in children with uCP with varying MACS levels is thus required.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, EEG can be used in measures that aim to combine alterations in electrocortical activity with the patient’s clinical deficits as assessed through clinical rating scales, an approach that has potential clinical significance. Of note, EEG has also been used to investigate the mechanisms of cortical plasticity in pathologies other than stroke, such as infantile cerebral palsy, where research showed that, in not-severely affected patients, the damaged hemisphere reorganises to compensate for the deficit (Inuggi et al 2018 ). This of course provided useful suggestions for specific rehabilitation protocols.…”
Section: Introductionmentioning
confidence: 99%